Construção do discurso e produção da legitimidade: o caso do hidrogênio verde no estado do Ceará, Brasil - Freitas, Felipe da Silva (2024)
The billion-dollar investments announced in the creation of hubs for the production and export of green hydrogen (H2V) will produce new forms of territorialization and energy accumulation, as well as create new and reconfigured industrial regions. In this scenario, the search for technological legitimacy presents itself as an essential process in the implementation and dissemination of new technologies, but its understanding is still limited when it comes to these new H2V centers, which have great potential to create new geographic spaces. Based on the adaptation of Suchman's (1995) concept of legitimacy, this work analyzed the process of producing technological legitimacy through discourses conveyed in the mass media, and its possible geographic implications, resulting from the investments announced in the H2V hub, located in the Pecém Industrial and Port Complex (CIPP), in the state of Ceará, Brazil. It is noted that interested parties have been committed to promoting the H2V value chain in the state mainly through public events, debates with decision makers, and the signing of memoranda of understanding (MOU) with national and international players, all of which were widely reported by local news outlets. Thus, the technical procedures of this research were based on qualitative analysis using qualitative data analysis software, ATLAS.ti, of a corpus with 498 articles from the newspapers Opovo and Diário do Nordeste, between November 2020 and August 2020. 2023, seeking to analyze in the public speeches of interested parties, elements that seek to establish legitimacy to the H2V scenario in the state of Ceará. Pragmatic legitimacy discourses emphasized the socioeconomic benefits linked mainly to the generation of employment and income. Discourses on moral legitimacy emphasized links to global efforts on climate change, renewable energy and institutional reforms to support the deployment of green hydrogen. Five main themes of cognitive legitimacy were identified: i) Territorial advantages; ii) Global leadership; iii) Break with the past; iv) Urgency of the moment and v) State action. With the results, it was concluded that the main actions of the State (Ceará and Brazil) shape the landscape and territory, and depend on multi-scalar interactions during the process of legitimizing sustainable energy systems. Starting from a geographic perspective, it is noted that stakeholders in the state of Ceará highlight the potential related to the H2V value chain, while minimizing or disregarding geographic issues related to the remodeling of new landscapes with the expansion of these renewable energy systems, considering the territorialization processes of energy infrastructures in traditional territories and the distribution and geographic dependence, at different scales, of decarbonized energy systems.